The economic impact of international remittances on poverty and household consumption and investment in Indonesia - Adams, Richard H., Jr (The World Bank, 2010)
This paper analyzes the impact of international remittances on poverty and household consumption and investment using panel data (2000 and 2007) from the Indonesian Family Life Survey. Three key findings emerge. First, using an instrumental variables approach to control for selection and endogeneity, it finds that international remittances have a large statistical effect on reducing poverty in Indonesia. Second, households receiving remittances in 2007 spent more at the margin on one key consumption good - food - compared with what they would have spent on this good without the receipt of remittances. Third, households receiving remittances in 2007 spent less at the margin on one important investment good - housing - compared with what they would have spent on this good without the receipt of remittances. Households receiving international remittances in Indonesia are poorer than other types of households, and thus they tend to spend their remittances at the margin on consumption rather than investment goods